Pervaporative transfer modeling through dense membranes validation of the scattered packet method - Essamri, Azzouz; El Gouri, Rachid; Zouair, F.Z; Cheikhi, Nabil; Hlou, Laamari (International Journal of Advanced Chemistry, 2014)
The study of the diffusion through a homogeneous dense film, covers practically and theoretically a fundamental interest. In pervaporation (membrane separation process) the diffusion is the limiting step in the operation of the transfer and thus directly influences the performance of the membrane. The knowledge of the diffusion coefficient of an aqueous solution in a membrane makes it possible to elucidate the mechanism of this elementary step of pervaporation. Several methods were used to determine the diffusivity of a compound through a dense membrane (differential permeation, kinetic of sorption). In this work, we tried to validate the method of the scattered packet. It is about a digital method, of cellular automaton, which produces really the process of diffusion through a membrane using the second law of Fick in which the diffusion coefficient is considered constant. Permeation flux data obtained by simulation allowed validating this method. By using the method of relaxation time and the method of maximum slope, can thus determine the coefficient of diffusion of diffusing species through the membrane. Keywords: Diffusivity, Membrane, Pervaporation, Scattered Packet Method.